Dissonance Between Parent‐Selected Bedtimes and Young Children's Circadian Physiology Influences Nighttime Settling Difficulties. Issue 4 (December 2013) - LeBourgeois, Monique K.; Wright, Kenneth P.; LeBourgeois, Hannah B.; Jenni, Oskar G.
ABSTRACT Nighttime settling difficulties (i.e., bedtime resistance, sleep‐onset delay) occur in about 25% of young children and are associated with attentional, behavioral, and emotional problems. We examined whether the timing of internal (endogenous) circadian melatonin phase (i.e., dim light melatonin onset; DLMO) and its relationship with parent‐selected bedtimes were related to nighttime settling behaviors. Fourteen regularly napping preschoolers (8 females; 30–36 months) participated in a 6‐day protocol (parent‐report of nighttime settling, actigraphic assessment of sleep onset latency, evening salivary DLMO). Average DLMO clock time was 07:40 p.m. ± 00:48 minutes, occurring 29 minutes ± 32 minutes prior to bedtime (lights‐out). Children with later DLMOs had longer sleep‐onset latencies (r = .62) and poorer success in falling asleep (r = −.59). Children whose bedtimes were closer to their DLMO had longer sleep‐onset latencies (r = .72) and increased bedtime resistance (r = −.54). We conclude that dissonance between parent‐selected bedtimes and children's circadian physiology may contribute to the development of nighttime settling difficulties in early childhood.